EFFECT OF CRUDE PALM OIL PROTECTION WITH FORMALDEHYDE ON HYDROGENATION OF RUMEN FLUID UNSATURATED FATTY ACID: ITS EFFECT ON BLOOD AND MEAT FATTY ACID - Nafly C. Tiven; Lies Mira Yusiati; Rusman Rusman; Umar Santoso (Universitas Gadjah Mada, 2013)
This research aimed to determine the effect of crude palm oil protected with formaldehyde on the hydrogenation of unsaturated fatty acids in the rumen and its effect on blood and meat fatty acids. Fifteenth local male lambs aged 9-12 months weighing 14-17 kg, were divided into 3 groups ration treatment. The first group received only the basal ration (R0), the 2nd group received the basal ration and 3% CPO (R1), while the 3rd group received the basal ration and 3% CPO protected with 2% formaldehyde (R2). Basal feed consisted of 60% grass, 30% bran and 10% soybean meal, with the nutrient content of 62.98% TDN, 45.5% DM, 14.48% CP, 4.70% EE and 21.93% CF. Parameters observed were the fatty acid from rumen fluid, blood and meat of sheep. Data were analyzed by complete randomized design direction patterns. Differences between treatments were tested further using Duncan's New Multiple Range Test. The results showed that treatment of R2 can increase unsaturated fatty acids in the rumen, blood and meat (P